COMPORTAMIENTO MICROESTRUCTURAL DEL ACERO AISI 1045 ENDURECIDO EN FRÍO Y TRACCIONADO / MICROESTRUCTURAL BEHAVIOUR OF THE STEEL AISI 1045 HARDENED AND STRESSED IN COLD CONDITIONS - FERNÁNDEZ COLUMBIÉ, TOMÁS; FERNÁNDEZ GUILARTE, ESTHER; RODRÍGUEZ GONZÁLEZ, ISNEL; ALCÁNTARA BORGES, DAYANIS; CASTILLO MATOS, RAMÓN (Revista de la Facultad de Ingeniería UCV, 2015)
El trabajo tiene como objetivo analizar el comportamiento del acero AISI 1045 sometido a deformado en frío con el empleode rodillo simple y luego traccionado. Se analiza el efecto de las imperfecciones cristalinas del material después de sersometido a ambos procesos de deformación y tracción. El diseño de experimento contempla las variables empleadas en elproceso de deformación, las cuales están relacionadas con la fuerza, el avance y el número de revoluciones. Se determina enlas microestructuras observadas, las imperfecciones en la estructura metalográfica con la reducción del tamaño promediode los granos producto de los efectos combinados de deformación tracción. Las probetas para la deformación plástica seprepararon según se establece para el ensayo de tracción tradicional; en este caso, la superficie se endureció con un rodillohasta lograr una dureza según fueron cambiadas las variables del proceso. La observación metalográfica se hizo posible através del encapsulado de las muestras ya que las mismas son de pequeños tamaños. ABSTRACT In this paper the analysis of the behaviour of the AISI 1045 steel subjected to cold deformation by using a simple rollerand then stressed, is carry out. It is also analyzed the effect of crystalline imperfections of this alloy being subjectedto hardened and both processes of deformation and traction. The experimental design takes into account the variablesemployed in the deformation process, which are related to the force, the displacement and the number of revolutions.The imperfections in the metallographic structure are determined by microscopic observation which allows assessing thereduction of the average size of grains due to the combined effects of the deformation and traction. The test tubes for thedeformation were prepared as indicated for traditional traction tests. In this study the surface was hardened using a rolleruntil achieving the specific hardness due to the changes on process variables. The metallographic observation becamepossible through the encapsulation of samples, due to their small sizes. Keywords: Microstructure, Cold deformation, Plastic deformation, Encapsulated, Simple roller.